A Case Series Study of Odontoid Fracture in the Elderly: A Severe Fracture Occurring Most Frequently in Osteoporotic Subjects. (10th January 2019) - Natella, Lauren; Bronsard, Nicolas; Allia, Jeremy; Hekayem, Laurent; Euller‐Ziegler, Liana; De Peretti, Fernand; Breuil, Véronique
ABSTRACT: The WHO definition of osteoporosis excludes cervical fractures. Recent studies suggest that atraumatic odontoid fractures (OF) may be favored by osteoporosis but global bone status for osteoporosis diagnosis has not been described. We present a case series of patients >65 years old hospitalized for low‐energy OF who had an evaluation of their bone status within 3 months after fracture, including clinical risk factors of osteoporosis, bone mineral density (BMD), vertebral fracture assessment (VFA) by dual X‐ray absorptiometry, and laboratory tests. Osteoporosis was defined as a T ‐score ≤ −2.5 on at least one site, or a bone fragility fracture associated with a T ‐score ≤ −1 at one site. Thirty‐three patients were hospitalized for OF, 30 of them as a consequence of a low‐energy impact: 20 women and 10 men (mean age: 85 years). Eight patients died before bone evaluation, four refused, and six were lost to follow‐up. Twelve patients were included: 11 women and one man (mean age: 83.8 years). Ten out of twelve patients fulfilled diagnostic criteria of osteoporosis, including eight with previous osteoporotic fractures (six severe fractures). Eight fulfilled specific treatment of osteoporosis criteria, but only two were treated. The mean follow‐up period was 12.2 ± 4.1 months. Prior to OF occurrence, all lived at home and were independent; at the time of discharge, six went to a nursing home. At 3 months of follow‐up ( n  = 10), one was dead and nine lived at home. At 12 months ( n  = 9), two were dead and seven lived at home. This study provides for the first time a classical evaluation of osteoporotic status for low‐energy OF in the elderly and shows that it occurs in osteoporotic subjects. These preliminary results require larger‐scale studies to determine whether OF could be considered as a severe osteoporotic fracture. © 2018 The Authors. JBMR Plus is published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.